A rule - based approach for converting Wikipedia content into semantic relations - Aydın, Nihal Yağmur. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
In this thesis, we propose a method for conversion from natural language into semantic relations. In this research, we focus on text written in highly unstructured form. The method is based on analysis of grammatical patterns of the sentences chosen from Wikipedia. Regular expressions are used for the generation of grammatical patterns. In addition to the grammatical structure of sentences, we also made use of the named entities to create semantic relations. Experiments on different types of relations showed that 71% and 82% success rates can be obtained for a threshold of 0.50 correctness rate.
Keywords: Wikipedia.; Electronic encyclopedias.; Computational linguistics.